SUPERVISION IN EDUCATIONAL ADMINISTRATION - Tini Mogea (FKIP, Universitas Palangka Raya, 2022)
Supervision is an effort to aid in the development and advancement of those under its supervision so that they can carry out predefined tasks efficiently and effectively. The characteristics and properties of supervision are both natural, which is a good thing. Supervision also includes the roles and responsibilities of a coordinator, consultant, group leader, and evaluator. The goal of supervision is to provide direct assistance to subordinates so that they have enough stock to complete tasks or jobs successfully, as well as to orient, train workers, lead, provide direction, and develop personnel skills.